Sorcery in the Framework of Folk Medicine on Siquijor Island - Ponteñila, Maria; Reynolds, Hubert (Silliman Journal, 2024)
Out of the 133 respondents (selected by stratified random sampling) interviewed, 92 believe sorcery exists on Siquijor Island and 97 saidpeople were afraid of it. Only 13, however believed that illnesses and deaths in Siquijor were due to sorcery. This finding seems to be inline with the observation that more people in the island are going to medical doctors. If a sick person believes the cause of his sickness is supernatural or Sorcery. he goes to the folk-healer (mananambal). If he believes the cause is natural, he goes to the medical doctor, according to this study.